Trust and Community Treatment Orders - McMillan, John; Lawn, Sharon; Delany-Crowe, Toni (Frontiers in Psychiatry, 2019)
There are conflicting views about the benefits of community treatment orders (CTOs) for people with mental illness. While there is a significant literature on the coercive nature of CTOs, there is less on the impact that CTOs have upon trust. A recovery-oriented approach requires a trusting therapeutic relationship and the coercion inherent in the CTO process may make it difficult for trust to be built, nurtured and sustained between workers and patients. Our aim was therefore to examine the role of trust within the CTO experience for mental health workers and patients on CTOs. Methods: We conducted a thematic discourse analysis of eight in-depth interviews with people who were currently on a CTO and 10 interviews with multi-disciplinary mental health workers in Adelaide, Australia (total N=18 interviews). The interviews were coded and analysed with the assistance of a patient representative. The findings reveal the challenges and opportunities for trust within the coercive relationship of a CTO. Findings: We found that patients have diverse experiences of CTOs and that trust or mistrust played an import role in whether or not they found the CTO beneficial.